The Effects of Colchicine on the Mitotic Behaviour of Selected Indigenous Tomato (Solanum Lycopersicum L.) Accession - Udofia, Ekaete George; Daudu, Oladipupo Yusuf; Isong, A. E; Odeyemi, Funnke; Adeboye, S. E.; Adeshina, D. A; Osisami, O. F.; Joseph, R. I. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Colchicine is one of the chemical mutagens that are widely used for inducing mutations in plants. This study was carried out to observe the mutagenic effect of colchicine on the chromosomal characteristic of tomato cells. Seeds of selected tomato accession (NG/SA/07/10/002-NorthEast) were treated with five different colchicine concentrations (0.1mM, 0.3mM, 0.5mM, 1.0mM) and 0.0mM as control. The cytological examination revealed that colchicine was found to induce changes in the chromosomal characteristics of tomato cells in the mitotic stage of development. Different types of chromosomal anomalies such as chromosomal clumping, condensation, fragmentation and chromosomal stickiness were observed. Somatic chromosome number were found to be 2n=24 in control cells and 2n=48 in colchicine treated cells indicating polyploidy.